Three little javelinas (The) - Lowell, Susan (New York : Scholastic Inc, 1992)
This is a southwestern adaptation of a familiar folktale: a chile-flavored "The Three Little Pigs." The story takes place in the Sonoran Desert, where Native American, Mexican, and Anglo cultures blend together.
Javelina (pronounced ha-ve-lee-na) comes from Spanish name for the collared pecary.
Keywords: Children stories-Fiction